Pelatihan Perpajakan Menggunakan Aplikasi Simulasi E-Faktur 3.0 (ALIFA 3.0) bagi Siswa SMA Negeri 6 di Kota Makassar - Imron Burhan; Sri Nirmala Sari; Ilham Ilham; Veronika Sari Den Ka; Rukminih Arifin; Nurul Afifah; Ardyansyah Gisda (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this Community Service is to increase the understanding and competence of High School Students (SMA) in the field of taxation, particularly related to E-Faktur. The method used in this service is a training method which includes socialization activities, practices, and assistance in using the E-Faktur Simulation Application 3.0 (Alifa 3.0). The evaluation instrument used in this activity is using a questionnaire and is analyzed descriptively. The results of this community service have an impact on increasing the knowledge and skills of participants in the field of taxation, especially related to Value-Added Tax (PPN) and E-Faktur.